Microstructures and mechanical properties of Cu-Sn alloy subjected to elevated-temperature heat deformation. (11th April 2018) - Hui, Jun; Feng, Zaixin; Fan, Wenxin; Wang, Pengfei
Abstract: Cu-Sn alloy was subjected to elevated-temperature isothermal compression with 0.01 s −1 strain rate and 500 ∼ 700 °C temperature range. The thermal compression curve reflected a competing process of work hardening versus dynamic recovery (DRV) and recrystallization, which exhibited an obvious softening trend. Meanwhile, high-temperature deformation and microstructural features in different regions of the alloy was analyzed through EBSD. The results show that grains grow as the temperature rises, competition among recrystallization, substructural, and deformation regions tends to increase with the increase of temperature, and distribution frequency of recrystallization regions gradually increases and then drops suddenly at 650 °C. At 500 ∼ 550 °C, preferentially oriented texturing phenomenon occurs, low angle boundaries(LABs) are gradually transformed into high angle boundaries (HABs) and the Σ (CSL) boundaries turn gradually into Σ3 boundaries. In tensile test of tin bronze, elongation at break increases slowly, whereas yield strength (YS) and ultimate tensile strength (TS) decrease gradually.